Bitter taste receptors of the zebra finch (Taeniopygia guttata) - Kumar, Praveen; Redel, Ulrike; Lang, Tatjana; Korsching, Sigrun I.; Behrens, Maik (Frontiers in Physiology, 2023)
Despite the important role of bitter taste for the rejection of potentially harmful food sources, birds have long been suspected to exhibit inferior bitter tasting abilities. Although more recent reports on the bitter recognition spectra of several bird species have cast doubt about the validity of this assumption, the bitter taste of avian species is still an understudied field. Previously, we reported the bitter activation profiles of three zebra finch receptors Tas2r5, -r6, and –r7, which represent orthologs of a single chicken bitter taste receptor, Tas2r1. In order to get a better understanding of the bitter tasting capabilities of zebra finches, we selected another Tas2r gene of this species that is similar to another chicken Tas2r. Using functional calcium mobilization experiments, we screened zebra finch Tas2r1 with 72 bitter compounds and observed responses for 7 substances. Interestingly, all but one of the newly identified bitter agonists were different from those previously identified for Tas2r5, -r6, and –r7 suggesting that the newly investigated receptor fills important gaps in the zebra finch bitter recognition profile. The most potent bitter agonist found in our study is cucurbitacin I, a highly toxic natural bitter substance. We conclude that zebra finch exhibits an exquisitely developed bitter taste with pronouced cucurbitacin I sensitivity suggesting a prominent ecological role of this compound for zebra finch.